A Behavioural Understanding of Privacy and its Implications for Privacy Law - Hughes, Kirsty (The Modern Law Review, 2012)
This article draws upon social interaction theory (the work of Irwin Altman) to develop a theory of the right to privacy, which reflects the way that privacy is experienced. This theory states that the right to privacy is a right to respect for barriers, and that an invasion of privacy occurs when a privacy barrier is penetrated. The first part of the paper establishes the position of the author's theory in the existing scholarship. The second part of the paper expands upon the theory to explain the nature of privacy barriers and the way that the author's theory manages a number of specific privacy issues, including threats to privacy, attempted invasions of privacy, unforeseeable interferences with privacy and waiving the right to privacy. The final part of the paper demonstrates the impact that this approach to privacy could have upon judicial reasoning, in particular Article 8 European Convention on Human Rights.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-2230.2012.00925.x